Development of Composite Microencapsulated Phase Change Materials for Multi-Temperature Thermal Energy Storage - Weiguang Su; Jo Darkwa; Tongyu Zhou; Dengfeng Du; Georgios Kokogiannakis; Yilin Li; Li Wang; Liying Gao (Crystals, 2023)
Phase change energy storage materials have been recognized as potential energy-saving materials for balancing cooling and heating demands in buildings. However, individual phase change materials (PCM) with single phase change temperature cannot be adapted to different temperature requirements. To this end, the concept of fabricating different kinds of microencapsulated PCM (MEPCM) and combing them to form a multiphase change material (MPCM) for multi-seasonal applications in buildings has been proposed. To prove the feasibility of this idea, three kinds of MEPCMs were fabricated and used for the development of three different composite MPCMs, classified as MPCM-1, MPCM-2, and MPCM-3. Analysis of the results shows that each MPCM sample was able to release latent heat at two different temperatures thus making them suitable for multi-temperature thermal energy storage applications. The phase change temperatures of the MPCMs were however found to be slightly reduced by 0.09–0.31 °C as compared with the MEPCMs samples. The measured energy storage capacities for the MPCMs were also reduced in the range of 6.3–11.4% as compared with the theoretical values but they displayed relatively good thermal stability behaviour of up to 197.8–218.8 °C. It was further identified that the phase change temperatures and latent heat of the MPCM was attributed to the weight percentages of individual components, as the theoretical values for the three MPCM samples were all in good accordance with the measured values. Therefore, optimizing the weight ratios of the MEPCM in MPCM samples and their corresponding thermophysical properties based on specific climatic conditions would be a necessary step to take in future investigations. Thermal performance enhancement of the MPCM is also being recommended as an essential part of further research.